The Solitary Wave Solutions for the Nonlinear Benjamin-Mahony Equation - Ibrahim, Salisu; Rasul, Rabar Mohammed (Communications in Mathematics and Applications, 2024)
The Benjamin-Bona-Mahony (BBM) equation is a nonlinear partial differential equation that describes the propagation of long waves in a shallow water channel. In this work, we present a comprehensive solution for the BBM equation using the Riccati-Bernoulli sub-ODE method. The method involves transforming the BBM equation into a Riccati equation, which is then further transformed into a Bernoulli equation. The Bernoulli equation is then solved analytically, and the solution is used to obtain the solution for the original BBM equation. Our results show that the Riccati-Bernoulli sub-ODE method provides an efficient and accurate solution for the BBM equation. The dfmethod can be extended to solve other nonlinear partial differential equations (NPDEs), making it a valuable tool for researchers in various fields.